2014
DOI: 10.1038/cdd.2014.172
|View full text |Cite
|
Sign up to set email alerts
|

Kit transduced signals counteract erythroid maturation by MAPK-dependent modulation of erythropoietin signaling and apoptosis induction in mouse fetal liver

Abstract: Signaling by the stem cell factor receptor Kit in hematopoietic stem and progenitor cells is functionally associated with the regulation of cellular proliferation, differentiation and survival. Expression of the receptor is downregulated upon terminal differentiation in most lineages, including red blood cell terminal maturation, suggesting that omission of Kit transduced signals is a prerequisite for the differentiation process to occur. However, the molecular mechanisms by which Kit signaling preserves the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 62 publications
4
35
0
Order By: Relevance
“…SCF/c-kit mutant and EPO-R deficient mice both exhibit severe anemia with varying erythroid progenitor defects, whereas erythropoiesis remains unaffected in the absence of IL-3R (31–33). Activating mutations in the c-kit receptor prevent erythroblast maturation, and expand progenitors (34*). Further, EPO acts directly on CFU-Es to promote survival as opposed to proliferation (35).…”
Section: Regulation Of Erythroid Progenitor Self-renewal Proliferatimentioning
confidence: 99%
“…SCF/c-kit mutant and EPO-R deficient mice both exhibit severe anemia with varying erythroid progenitor defects, whereas erythropoiesis remains unaffected in the absence of IL-3R (31–33). Activating mutations in the c-kit receptor prevent erythroblast maturation, and expand progenitors (34*). Further, EPO acts directly on CFU-Es to promote survival as opposed to proliferation (35).…”
Section: Regulation Of Erythroid Progenitor Self-renewal Proliferatimentioning
confidence: 99%
“…Combining phosphoproteomics and a functional screen, our data highlights a general decrease in kinase activity across the erythroid proteome during terminal maturation and in particular a critical role for downregulation of Ras/MAP kinases activity is suggested. Previous studies have demonstrated defective terminal maturation in systems expressing either constitutively active forms of c-Kit or Ras proteins (Haas et al, 2015;Matsuzaki et al, 2000). Our systems-wide analysis of erythropoiesis derived from primary healthy donor human CD34 + cells suggests c-Kit drives expansion of early erythroid precursors and inhibits terminal maturation via Ras/MAPK signaling whereas EPOR drives signaling predominantly via the JAK-STAT5 pathway to foster later stages of terminal maturation.…”
Section: Discussionmentioning
confidence: 74%
“…Our erythroid culture system contained both SCF (c-Kit Ligand) and EPO in the first and second phase (day0-7) and EPO only in the third phase (day12-14) ( Figure 1A). The rationale for this culture system is based on findings that persistently elevated SCF-c-Kit signaling inhibits terminal erythroid maturation (Haas et al, 2015;Muta et al, 1995). The levels of c-Kit and EPOR/JAK2 proteins decreased during differentiation but with differing kinetics (Figures 6D).…”
Section: System-wide Dissection Of C-kit and Epor Phosphosignaling Inmentioning
confidence: 99%
“…A variety of mechanisms are in place to control the erythroid cell response to cytokines, and it would not be surprising if major additional mechanisms remain to be discovered. As cellular responses to cytokines can depend on the maturation status of the cells [2729], this protocol provides a sensitive assay to quantitate cellular responses to cytokine signals in specific cell types delineated by their ensemble of cell surface proteins detected by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%